NISBAH DAUN BATANG, NISBAH TAJUK AKAR DAN KADAR SERAT KASAR ALFALFA (Medicago sativa) PADA PEMUPUKAN NITROGEN DAN TINGGI DEFOLIASI BERBEDA - Rahmawati, Viata; Sumarsono, Sumarsono; Slamet, Widyati (Animal Agriculture Journal, 2013)
ABSTRACTThe study aimed to determine the effect of nitrogen fertilization and defoliation of different height to the leaf stem ratio, shot root ratio and crude fiber content in alfalfa plants (Medicago sativa). This research used factorial randomized block design (FRBD) 4x2 with 3 replicate. The main factor is the dose of nitrogen fertilization (0, 30, 60, 90 kg N/ha), the second factor is the heigth of the defoliation (5 and 10 cm). Parameters measured were leaf stem ratio, shot root ratio and crude fiber content of alfalfa. The results showed that there was no effect of nitrogen fertilization and defoliation high contrast ratio of leaf to stem, shot root ratio and crude fiber content of alfalfa. Data were analyzed with the results of research based on the F test of variance procedure and Duncan's multiple range test. The results showed that there was no effect of nitrogen fertilization and different defoliation height to leaf stem ratio, shoot root ratio and crude fiber of alfalfa. There are indication that leaf stem ratio and shoot root ratio obtained the best results in the treatment of nitrogen fertilization of 30 kg N/ha and defoliation height of 5 cm.Keywords: alfalfa, nitrogen fertilization, high defoliation, leaf stem ratio, shot root ratio, crude fiberABSTRAKPenelitian bertujuan untuk mengetahui pengaruh pemupukan nitrogen dan tinggi defoliasi yang berbeda terhadap nisbah daun batang, nisbah tajuk akar dan kadar serat kasar pada tanaman alfalfa (Medicago sativa). Penelitian ini menggunakan rancangan acak kelompok (RAK) pola faktorial 4x2 dengan 3 ulangan. Faktor utama adalah dosis pemupukan nitrogen (0, 30, 60, 90 kg N/ha), faktor kedua adalah tinggi defoliasi (5 dan 10 cm). Parameter yang diamati adalah nisbah daun batang, nisbah tajuk akar dan kadar serat kasar alfalfa. Data diolah dengan menggunakan analisis ragam dan uji wilayah ganda Duncan. Hasil penelitian menunjukkan bahwa tidak ada pengaruh pemberian pemupukan nitrogen dan tinggi defoliasi berbeda terhadap nisbah daun batang, nisbah tajuk akar dan kadar serat kasar alfalfa. Ada indikasi nisbah daun batang dan nisbah tajuk akar hasil terbaik diperoleh pada perlakuan pemupukan nitrogen 30 kg N/ha dan tinggi defoliasi 5 cm.Kata kunci: alfalfa, pemupukan nitrogen, tinggi defoliasi, nisbah daun batang, nisbah tajuk akar, serat kasar